Tibiotalar Joint Contact Mechanics Following Syndesmosis Fixation with Screws Versus a Flexible Fixation Device (TightRope™). Issue 4 (16th October 2019) - Pang, Eric; Bedigrew, Katherine; Behn, Anthony; Chou, Loretta; Hunt, Kenneth; Palanca, Ariel
Category: Ankle, Arthroscopy, Trauma Introduction/Purpose: Background: A shift and increase in mean tibiotalar contact pressure has been demonstrated in simulated syndesmotic injuries. The effect of screw fixation and/or suspensory fixation on restoration of pressure mechanics in the setting of a syndesmotic injury remains largely unknown. Hypothesis/Purpose: The purpose of this study is to examine the contact mechanics of the tibiotalar joint following syndesmosis fixation with screws versus a flexible fixation device for complete syndesmotic injury. Methods: Six matched pairs of cadaveric below knee specimens were randomly assigned fixation with either two 3.5 mm cortical screws or two TightRopes™ (Arthrex). Motion capture trackers were fixed to the tibia, fibula, and talus and a pressure sensor was placed in the tibiotalar joint. Each specimen was first tested intact with an axial compressive load followed by external rotation torque while maintaining axial compression. The syndesmosic ligaments were then completely sectioned and subsequently repaired with either two TightRopes™ or two screws and the protocol was repeated. Mean contact pressure (MCP), peak pressure (PP), reduction in contact area (CA), translation of the center of pressure (COP), and relative talar and fibular motion were calculated. Specimens were then cyclically loaded in external rotation to failure. Comparisons were made using paired t-tests and/or Welch's t-tests. Results: No differences in MCP, PP, or CA were observed between the intact and instrumented states during AL alone for either group. MCP relative to intact testing was increased in the screw group at 5 Nm (4.8±4.1 MPa vs 3.6±0.8 MPa, p=0.033) and 7.5 Nm torque (6.2±1.4 MPa vs 4.2±1.2 MPa, p=0.024). Likewise, PP was increased in TightRope™ group at 7.5 Nm torque (14.4±3.1 MPa vs 10.8±1.6 MPa, p=0.046). There was no change in COP in the TightRope™ group at any threshold; however, at every threshold tested there was significant medial and anterior COP translation in the screw group relative to the intact state. Conclusion: Either screws or TightRope™ fixation is adequate with AL alone. With lower amounts of torque, the TightRope™ group exhibits contact and pressure mechanics that more closely match native mechanics.